PKM Expanding Market Share through Training On-Line Sales for Producers of Kripik Cassava in Kotaanyar Probolinggo - Musthafa Syukur; A. Redho Bastian; Abd. Malik; Issadur Rofik; Rohikin Makhtum; Rahmat Mashura; Firman Firman (GUYUB: Journal of Community Engagement, 2021)
The purpose of online sales training for producers of various chips at Kotaanyar, Probolinggois to help these businesses out of the difficulty to expand market share. This training elaborates how to do online sales and create marketing networks become more widespread due to this training. Based on observations, all the craftsmen still apply conventional marketing its range is limited. It means that the marketing strategies implemented are still out of date. Meanwhile, many competitors have implemented modern information technology. Therefore, online sales training can assist the craftsmen in extending market share, reducing the cost of logistics and also other distribution costs. Further, this training proved beneficial for management to improve profitability. In addition, this sales-driven information technology can also reduce marketing costs significantly. In short, based on the observation, post-training provided the benefits of increased sales, which contribute to the sustainability of the producers of cassava chips at Kotaanyar, Probolinggo.